2020
DOI: 10.3390/ma13204669
|View full text |Cite
|
Sign up to set email alerts
|

Ground Tire Rubber Modified by Ethylene-Vinyl Acetate Copolymer: Processing, Physico-Mechanical Properties, Volatile Organic Compounds Emission and Recycling Possibility

Abstract: Ground tire rubber (GTR) was reclaimed and modified with 10 phr of ethylene-vinyl acetate copolymer via low-temperature extrusion process. Processing, physico-mechanical properties, volatile organic compounds emission, and recycling possibility were investigated. In order to better understand the impact of used modifiers, their efficiency was compared with trans-polyoctenamer, which is an additive that is commercially dedicated to waste rubber recycling. The results showed that a relatively small amount of eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…The tensile properties of the GTR modified EVA copolymers in most compositions an exception was the sample with 2.5 phr of EVA-39%) were higher compared to the reference sample (GTR DCP ). Moreover, the prepared modified GTR showed tensile properties comparable or even higher than those of commercially available reclaimed rubbers (~4-5 MPa) [30], which fully justifies the application of GTR modification.…”
Section: Vocs' Emission Profiles Determined For Modified Gtrsupporting
confidence: 51%
See 1 more Smart Citation
“…The tensile properties of the GTR modified EVA copolymers in most compositions an exception was the sample with 2.5 phr of EVA-39%) were higher compared to the reference sample (GTR DCP ). Moreover, the prepared modified GTR showed tensile properties comparable or even higher than those of commercially available reclaimed rubbers (~4-5 MPa) [30], which fully justifies the application of GTR modification.…”
Section: Vocs' Emission Profiles Determined For Modified Gtrsupporting
confidence: 51%
“…Our previous work [30] showed that using of a relatively small amount (10 phr) of ethylene-vinyl acetate copolymer during low-temperature devulcanization resulted in the improvement of the tensile properties of the modified reclaimed GTR, which were also higher compared to GTR modified by trans-polyoctenamer (an additive commonly used in waste rubber recycling). Furthermore, the results showed that using of thermoplastics in GTR limits the emission of volatile organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Such a low value points to the efficient polymerization of the system and a low portion of unbound extractives [ 76 ]. Higher sol fraction contents for composite foams are attributed to the noticeably higher value of this parameter for GTR itself (even over 10% [ 34 , 77 ]), as well as to the GTR interactions with the polyurethane matrix. The functional groups present on the surface of rubber particles (see GTR hydroxyl values in Table 2 ) may interact with isocyanates present in the polyurethane system, resulting in partially loose polyols macromolecules [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the whole process (extrusion with specific screws configuration) generates shear forces adding additional energy to the system. In the work of Zedler et al [34], research was conducted on extrusion of modified rubber. The temperature settings of the Table 2 presents the properties of modified GTR samples, including the hydroxyl values (L OH ) determined according to the method based on the modified test method for isocyanate groups, as described in our previous works [28,29].…”
Section: Modifications Of Ground Tire Rubbermentioning
confidence: 99%
See 1 more Smart Citation